Inhibitory effect of positively charged triazine antagonists of prokineticin receptors on the transient receptor vanilloid type-1 (TRPV1) channel. (September 2015) - De Petrocellis, Luciano; Schiano Moriello, Aniello; Byun, Joon Seok; Sohn, Joo Mi; Lee, Jae Yeol; Vázquez-Romero, Ana; Garrido, Maria; Messeguer, Angel; Zhang, Fang-Xiong; Zamponi, Gerald W.; Deplano, Alessandro; Congiu, Cenzo; et al.
Graphical abstract: Four positively charged compounds previously shown to produce analgesic activity by interacting with prokineticin receptors or T-type calcium channels, inhibited capsaicin-induced and TRPV1-mediated elevation of intracellular Ca 2+ in HEK-293 (left). KYS-05090 showed the highest potency as a TRPV1 antagonist, even higher than that the open-pore triazine TRPV1 inhibitor, 8aA . Electrophysiological experiments (right) showed that TRPV1-positive mouse sensory neurons exhibit significantly reduced capsaicin-evoked currents after pre-incubation with KYS-05090 . Abstract: Four positively charged compounds, previously shown to produce analgesic activity by interacting with prokineticin receptor or T-type calcium channels, were tested for their ability to inhibit capsaicin-induced elevation of intracellular Ca 2+ in HEK-293 cells stably transfected with the human recombinant TRPV1, with the goal of identifying novel TRPV1 open-pore inhibitors. KYS-05090 showed the highest potency as a TRPV1 antagonist, even higher than that of the open-pore triazine inhibitor 8aA . The latter showed quite remarkable agonist/desensitizer activity at the rat recombinant TRPM8 channel. The activity of KYS-05090 and the other compounds was selective because none of these compounds was able to modulate the rat TRPA1 channel. Open-pore inhibitors of TRPV1 may be a new class of multi-target analgesics with lesser side effects, such as loss of acute pain sensitivity and hyperthermia, than most TRPV1 antagonists developed so far.